Flobots: Robotic flowers for bee behaviour experiments - Essenberg, Carla Jean (Journal of Pollination Ecology, 2015)
Studies of pollinator foraging behaviour often require artificial flowers that can refill themselves, allowing pollinators to forage for long periods of time under experimental conditions. Here I describe a design for inexpensive flowers that can refill themselves upon demand and that are easy enough to set up and clean that they can be used in arrays of 30 or more flowers. I also summarize of a variety of artificial flower designs developed by other researchers.